Ractopamine and lysine levels on performance and carcass characteristics of finishing pigs - Almeida,Erin Caperuto de (2010)
It was evaluated the effect of diets supplemented or not supplemented with ractopamine and digestible lysine on the performance and carcass characteristics of finishing pigs. A total of 50 barrows and 50 gilts (90.2 kg ± 3.5 kg) were used. In the growth performance trial, a randomized block design was utilized in a 5 x 2 factorial arrangement, consisting of five levels of digestible lysine (0.68; 0.78; 0.88; 0.98 and 1.08%) and two levels of ractopamine (0 and 5 ppm), totaling ten diets and five replications. In a study of carcass characteristics, the same design and levels of lysine and ractopamine were used, but another factor (sex of animals- female and male) was included, totaling 20 treatments, each one with five replicates. Except for lysine daily intake, it was not observed effect of levels of digestible lysine. The supplementation with ractopamine improved daily weight gain and feed conversion but it did not affect the average feed intake. A greater loin depth and higher yield of carcass meat was obtained in gilts, regardless to supplementation with ractopamine, and also in the males fed ractopamine. The ractopamine improved the rib-eye area but it did not affect the yield and carcass length neither thickness of subcutaneous fat. The levels of digestible lysine did not affect carcass characteristics in either sex. It was found that sex had effect on backfat thickness, which was lower in the carcasses of gilts. The use of 5 ppm ractopamine improves animal performance and carcass characteristics of barrows. The level of 0.68% digestible lysine is sufficient for pigs of both sexes fed diets supplemented with or without ractopamine to show maximal performance and a good carcass composition.